Prevalence of high-risk group for obstructive sleep apnea using the STOP-Bang questionnaire and its association with cardiovascular morbidity - Kang, Jieun; Koo, Hyeon-Kyoung; Kang, Hyung Koo; Seo, Woo Jung; Kang, Jiyeon; Kim, Jinseob (Frontiers in Neurology, 2024)
ObjectivesObstructive sleep apnea (OSA) is a common sleep-related breathing disorder, yet many cases remain undiagnosed. The STOP-Bang questionnaire was developed to identify individuals at high risk of OSA. We aimed to investigate the prevalence of individuals with suspected OSA using the STOP-Bang risk stratification in the general population of South Korea. Additionally, we determined if the STOP-Bang risk stratification independently predicts cardiovascular morbidity.MethodsData from the eighth Korea National Health and Nutrition Examination Survey (2019–2020) were used. Participants aged ≥40 with complete data for STOP-Bang questionnaire were included. A STOP-Bang score of ≥5 classified individuals as high-risk whereas scores of 3–4 and less than 3 classified them as intermediate- and low-risk, respectively. The association between the high-risk group and cardiovascular morbidity was analyzed using complex sample logistic regression.ResultsAmong the 6,630 participants included, approximately 6.7% were classified as high-risk based on the STOP-Bang questionnaire. The prevalence of diagnosed OSA in the high-risk group was 4.0%. The high-risk group showed a significantly higher prevalence of cardiovascular morbidity (11.9%) compared to those in the low- and intermediate-risk groups (3.0 and 8.1%, respectively). After adjusting for variables associated with cardiovascular risk, the high-risk group remained an independent predictor of increased likelihood of cardiovascular morbidity compared to the low-risk group (odds ratio, 2.05; p = 0.002). When stratified by sex, STOP-Bang high-risk was significantly associated with cardiovascular morbidity in men; however, the same trend was not observed in women.ConclusionWe found a significant proportion of individuals at high risk of OSA is likely to remain undiagnosed in the general population of South Korea. The high-risk group demonstrated a higher burden of cardiovascular morbidity, and the STOP-Bang high-risk group was an independent predictor of cardiovascular morbidity.